CoBr2-catalyzed straightforward synthesis of quinoxalines via dehydrogenative coupling strategy - Dubey, Shivansh; Punji, Benudhar (Chemistry-an Asian Journal, 2025)
Establishing a benign and straightforward protocol for synthesizing biorelevant and synthetically valuable quinoxaline is very important. Herein, we report a simple and efficient protocol for the sustainable synthesis of diverse quinoxaline derivatives catalyzed by cobalt salt. The reaction proceeds through the dehydrogenative coupling of alkyl and aryl ethane 1,2-diols with aryl diamines in the presence of a catalytic CoBr2/K2CO3. The usage of the greener solvent 2-MeTHF and the release of H2 and H2O as the sole byproducts make the process advantageous. The protocol led to the synthesis of diverse quinoxalines bearing synthetically useful functionalities, such as fluoro, chloro, bromo, cyano, trifluoromethyl, and ether. The reaction is presumed to proceed via the dehydrogenative-condensation pathway involving a cobalt-hydride intermediate.
Keywords: cobalt; dehydrogenative coupling; heterocycles; ligand-free process; Quinoxaline